2020
DOI: 10.1111/pbr.12847
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of candidate genes associated with resistance to soybean rust (Phakopsora pachyrhizi) in line UG‐5

Abstract: Online databases containing genetic information are crucial to extract new candidate genes from existing data and web‐based resources. The objective of this study was, therefore, to predict putative candidate genes associated with resistance to SBR in line UG‐5 and understand their functions using different bioinformatics tools from the online available databases. The physical positions for the flanking markers of the identified putative QTLs were searched on the SoyBase database genome browser based on Glyma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Yamanaka et al (2015) and Aoyagi et al (2020) found in the accessions Xiao Jing Huang, Himeshirazu and WC2 single genes for resistance to ASR, which share the same positions as Rpp1, between Sct_187 and Sat_064, and a similar reaction pro le against P. pachyrhizi inoculum. Conversely, Hossain et al (2015), Yamanaka et al (2016), Gebremedhn et al (2018Gebremedhn et al ( , 2020 and Chen et al (2015) identi ed in the genotypes PI 587905, PI 594767A, PI 587855, UG-5 and SX6907 resistance genes in similar location as Rpp1-b, between Sat_372 and Sat_064. Rocha et al (2016) also studied the reaction of PI 594767 A, however using an isolate (PPUFV02) different from the one used by Hossain et al (2015).…”
Section: Introductionmentioning
confidence: 93%
“…Yamanaka et al (2015) and Aoyagi et al (2020) found in the accessions Xiao Jing Huang, Himeshirazu and WC2 single genes for resistance to ASR, which share the same positions as Rpp1, between Sct_187 and Sat_064, and a similar reaction pro le against P. pachyrhizi inoculum. Conversely, Hossain et al (2015), Yamanaka et al (2016), Gebremedhn et al (2018Gebremedhn et al ( , 2020 and Chen et al (2015) identi ed in the genotypes PI 587905, PI 594767A, PI 587855, UG-5 and SX6907 resistance genes in similar location as Rpp1-b, between Sat_372 and Sat_064. Rocha et al (2016) also studied the reaction of PI 594767 A, however using an isolate (PPUFV02) different from the one used by Hossain et al (2015).…”
Section: Introductionmentioning
confidence: 93%
“…Yamanaka et al (2015) and Aoyagi et al (2020) found in the accessions Xiao Jing Huang, Himeshirazu and WC2 single genes for resistance to ASR, which share the same positions as Rpp1, between Sct_187 and Sat_064, and a similar reaction pro le against P. pachyrhizi inoculum. Conversely, Hossain et al (2015), Yamanaka et al (2016), Gebremedhn et al (2018Gebremedhn et al ( , 2020 and Chen et al (2015) identi ed in the genotypes PI 587905, PI 594767A, PI 587855, UG-5 and SX6907 resistance genes in similar location as Rpp1-b, between Sat_372 and Sat_064. Rocha et al (2016) also studied the reaction of PI 594767 A, however using an isolate (PPUFV02) different from the one used by Hossain et al (2015).…”
Section: Introductionmentioning
confidence: 94%
“…Another promising strategy for sustainable and effective SBR resistance is to utilize alternative R gene combinations and dynamic turnover in the field ( Childs et al., 2018a ). However, the identity of these Rpp genes needs to be revealed ( Gebremedhn et al., 2020 ). Under the current conditions, it is also impractical to rely only on several major genes or combinations of these genes to control the SBR disease in field production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to major genes, many recent molecular studies have revealed more disease-resistant pathways in soybeans ( Childs et al., 2018b ). The resistance usually occurs in the form of signals, transcription factors, NB-LRR, or secondary metabolites ( Gebremedhn et al., 2020 ; Waheed et al., 2021 ). They usually improve not only the resistance to a particular pathogen but the overall resistance of the plant as well.…”
Section: Introductionmentioning
confidence: 99%